Pityriasis versicolor: insight into current knowledge and treatment possibilities - Parys, Jakub; Mikosińska, Agnieszka; Kaźmierczak, Martyna; Kałuziak, Patrycja; Mossakowski, Maciej; Jajczak, Marta; Witek, Aleksandra; Jesionek, Stanisław; Litwin, Mateusz (Journal of Education, Health and Sport, 2025)
Background: Pityriasis versicolor is a prevalent superficial mycosis caused by saprophytic yeasts of the Malassezia genus. It primarily affects adolescents and young adults, presenting as hypo- or hyperpigmented macules on the skin, commonly located on the trunk and upper arms. While various topical and systemic antifungal treatments are available, high relapse rates remain a significant clinical challenge. The condition often leads to psychological distress due to visible lesions on the skin surface. Aim of the study: Given its high prevalence (reaching up to 50% in some tropical regions) and its psychosocial implications, pityriasis versicolor remains a critical dermatological concern. This study aims to synthesize current medical knowledge about the condition, focusing on the efficacy, indications, and limitations of available treatment options, especially in addressing recurrent cases. State of knowledge: Pityriasis versicolor is well-characterized in terms of its etiology and clinical manifestations. Numerous therapeutic interventions have been investigated, ranging from topical agents like azoles or terbinafine to systemic treatments such as itraconazole and fluconazole. Despite these advancements, a universally accepted gold standard for treatment remains undefined, and patient adherence often is a barrier to successful outcomes. Conclusion: Despite significant progress in understanding and managing pityriasis versicolor, further research is essential. Future efforts should aim to optimize treatment efficacy, reduce relapse rates, and minimize adverse effects. Randomized controlled trials with larger and more diverse populations are particularly needed to establish standardized protocols and explore innovative therapies, including prophylactic measures and targeted treatments.